Legal Counseling: Preventing Crime through a Local Wisdom Approach: Penyuluhan Hukum: Mencegah Kejahatan melalui Pendekatan Kearifan Lokal - Salam, Safrin; Suhartono, Rizki Mustika; Karim, La Ode Muhammad; Yusran, Yusran; Azhar, Eko (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article aims to explore the role of local wisdom in strengthening law enforcement and preventing crime in Buton community. By employing a research methodology adhering to academic standards, the study identifies the forms of local wisdom and its implications for crime prevention. The research findings highlight the significance of cultural festivals, particularly the